Pengurusan - Ab. Wahab Mat; Shahrol Aman Ahmad; Azahari Ramli; Abu Mansor Ahmad (McGraw-Hill, 2007)
Buku ini mengetengahkan prinsip-prinsip asas, konsep-konsep penting dan amalan-amalan pengurusan organisasi.